2013
DOI: 10.1098/rspb.2012.2852
|View full text |Cite
|
Sign up to set email alerts
|

A window on the past: male ornamental plumage reveals the quality of their early-life environment

Abstract: It is well established that the expression of many ornamental traits is dependent on the current condition of the bearer. However, conditions experienced in early life are also known to be important for an individual's subsequent fitness and therefore, directly or indirectly, for the fitness of their mate. Specifically, a recent hypothesis suggests that sexually selected traits might be sensitive to conditions experienced during early-life development and thereby function as honest indicators of developmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…Experimental manipulation of dietary carotenoids in hihi ( Notymystis cincta ) nestlings influenced the color of adult white ear tufts, but did not impact juvenile or adult carotenoid‐ or melanin‐based colors (Walker et al. ). Additionally, longitudinal studies have demonstrated condition and age effects for carotenoid‐based (Evans and Sheldon ), structural (Siefferman et al.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental manipulation of dietary carotenoids in hihi ( Notymystis cincta ) nestlings influenced the color of adult white ear tufts, but did not impact juvenile or adult carotenoid‐ or melanin‐based colors (Walker et al. ). Additionally, longitudinal studies have demonstrated condition and age effects for carotenoid‐based (Evans and Sheldon ), structural (Siefferman et al.…”
Section: Introductionmentioning
confidence: 99%
“…. Although sexual dichromatism can be functional1444454647, and is often the object of female choice, one single subtle sexually dichromatic trait might not provide sufficient information about the carrier to be useful. Species may therefore evolve the use of multiple characteristics to evaluate conspecifics.…”
Section: Discussionmentioning
confidence: 99%
“…When combined with the findings that males’ colouration was no more variable in males than females’, this suggests that differences in colour between sexes in our species might not be shaped by the forces of sexual selection alone. As well as being the object of female choice, sexually dichromatic traits have been proved to function in quality signaling4547 and agonistic interactions in several avian species144446.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies documenting the effects from early conditions refer to impacts on fitness caused by nutritional deficiencies, parasite infestations, or extreme temperatures during development (Buchanan et al 2003, Gluckman et al 2005, Ardia et al 2010, Walker et al 2013. Any perturbation during development may have deleterious consequences on growth, immune system, and the neural functions of juvenile individuals, which may then impair the subsequent phases of annual and/or life cycle events (Lindström 1999, Lummaa and Clutton-Brock 2002, Monaghan 2008).…”
mentioning
confidence: 99%